2023
DOI: 10.1111/jpn.13879
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental impact of silymarin in growing pig diet on the growth performance, total tract digestibility, faecal microflora, faecal noxious gas emission and absorption rate in blood

Md Mortuza Hossain,
Hyung Suk Hwang,
Se Yeon Jang
et al.

Abstract: The research was done to examine the impact of dietary silymarin on growth performance, total tract digestibility, faecal microbial, faecal gas emission and absorption rate in blood of growing pigs. Experiment 1: a total of 140 growing pigs (24.47 ± 2.49 kg) were used in a 6‐week trial. There were four dietary treatment groups (seven replicate pens/treatment, five pigs/pen) and treatment diets composed of corn, soybean meal (SBM), distillers dried grains with solubles (DDGS), and rapeseed meal‐based basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The mixture of probiotic and phytogenic (0.1%, 0.2%, and 0.3%) supplements into broiler diets linearly improved overall growth performance (BWG and FI), immunological health, and favourable microbiological conditions while having no detrimental effects on nutrient digestibility or meat quality (Biswas & Kim, 2023c). The incorporation of PFA (silymarin) into a diet based on corn‐soybean‐rapeseed meal enhanced growth, digestibility, faecal microbiota, and the absorption rate in the blood of growing pigs (Hossain et al, 2023). There have been observations regarding interactions between substances in the feed matrix, such as PFA's biological effects being lessened when present in high‐protein or fibrous diets (Beauchemin & McGinn, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The mixture of probiotic and phytogenic (0.1%, 0.2%, and 0.3%) supplements into broiler diets linearly improved overall growth performance (BWG and FI), immunological health, and favourable microbiological conditions while having no detrimental effects on nutrient digestibility or meat quality (Biswas & Kim, 2023c). The incorporation of PFA (silymarin) into a diet based on corn‐soybean‐rapeseed meal enhanced growth, digestibility, faecal microbiota, and the absorption rate in the blood of growing pigs (Hossain et al, 2023). There have been observations regarding interactions between substances in the feed matrix, such as PFA's biological effects being lessened when present in high‐protein or fibrous diets (Beauchemin & McGinn, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, silybin possesses a wide range of pharmacological activities, such as hepatoprotective, anti-inflammatory, and antibacterial activities [ 11 , 12 ], and improves mitochondrial function by regulating biogenesis and bioenergetics [ 13 , 14 ]. Dietary silymarin/silybin has been reported to improve growth performance and exert a promoting effect on systemic health in pigs and poultries [ 15 , 16 , 17 , 18 ]. Consistently, our previous research also found that dietary silybin decreased diarrhea incidence and improved growth performance in weaned piglets; moreover, silybin supplementation effectively alleviated intestinal injury by improving the antioxidant properties, mitochondrial function, and microbial community composition of weaned piglets [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…for example, silymarin, gallic acid, Achyranthes japonica extract, turmeric, ginseng, and so forth (Biswas et al, 2023;Hossain et al, 2024;Khan et al, 2023). One of them, silymarin, has gained research attention and practical applications in the poultry industry over the past few years (Surai & Peter, 2023).…”
mentioning
confidence: 99%